2023
DOI: 10.1111/joim.13742
|View full text |Cite
|
Sign up to set email alerts
|

Splenectomy outcomes in immune cytopenias: Treatment outcomes and determinants of response

Olisaemeka D. Ogbue,
Waled Bahaj,
Tariq Kewan
et al.

Abstract: BackgroundSplenectomy is commonly used to treat refractory immune–mediated cytopenia, but there are no established factors that are associated with response to the procedure.ObjectivesA cohort study was conducted to evaluate the hematologic and surgical outcomes of splenectomy in adult patients with immune cytopenias and identify preoperative factors associated with response.MethodsData from the Cleveland Clinic Foundation for 1824 patients aged over 18 who underwent splenectomy from 2002 to 2020 were analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 55 publications
(48 reference statements)
0
4
0
Order By: Relevance
“…Although splenectomy was used for years with immense success, it is rarely used today [3,60]. In a recent cohort study of 1824 patients, splenectomy was found to be an effective treatment, though with surgical complications in 12% [69].…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Although splenectomy was used for years with immense success, it is rarely used today [3,60]. In a recent cohort study of 1824 patients, splenectomy was found to be an effective treatment, though with surgical complications in 12% [69].…”
Section: Treatmentmentioning
confidence: 99%
“…Cold-antibody autoimmune hemolytic anemia, referred to as cold agglutinin syndrome (CAS) or cold agglutinin disease (CAD), is a rare autoimmune condition characterized by the presence of high levels of cold-sensitive autoantibodies in the blood, primarily IgM, as well as autoantibodies that remain active at temperatures below 30 • C (86 • F) [3,12,20,[70][71][72][73][74][75][76]. The antibodies have a particular affinity for red blood cells, often the Ii RBC antigens [3,12,77,78], causing them to aggregate (agglutination), activate the complement system, and undergo intra-and/or extravascular hemolysis [3,12,20,[67][68][69][70][71][72][73][74][75][76][77]. Historically, CAD included both CAD and CAS; however, these two conditions are now recognized as different and have been separated into distinct entities.…”
Section: Cold-antibody Autoimmune Hemolytic Anemiamentioning
confidence: 99%
“…Although splenectomy was used for years with immense success, it is rarely used today [3,60]. In a recent cohort study of 1824 patients, splenectomy was found to be an effective treatment, though with surgical complications in 12% [69].…”
Section: Treatmentmentioning
confidence: 99%

Autoimmune Hemolytic Anemias

Loriamini,
Cserti-Gazdewich,
Branch
2024
Preprint
“…It is in this context of the absence of planned prospective data collection in this arena that, in this issue of the Journal of Internal Medicine, Ogbue et al provide crucial insights of their institutional experience with splenectomy in the treatment of patients with a variety of autoimmune cytopenias at the Cleveland Clinic, an institution in the United States with a deep commitment to clinical excellence [9]. The authors meticulously applied thoughtful exclusion criteria through a retrospective evaluation of 1824 consecutive splenectomy cases across the years 2002-2020 to properly isolate 339 patients who underwent splenectomy for one of the following autoimmune pathology-proven discordant diagnoses appropriately removed from effectiveness metrics (Fig.…”
mentioning
confidence: 99%